Strategic Alignment of Eco-Practices: The Mediator of Eco-Controls in Translating Environmental Strategy - Sannamwong, Kanya; Wongkaew, Wila-sini; Hoonsopon, Danupol (Creative Business and Sustainability Journal, 2023)
This study aims to explore the role of eco-controls in translating competitive environmental strategic intents into eco-practices, as well as the associations between eco-practices and environmental and economic performance. A web-based survey is used to collect data from Thai manufacturing firms in high-polluting industries. Structural Equation Modeling (SEM) is employed for data analysis. Findings from the study show most firms use more bureaucratic forms of eco-control (151 out of 169 firms). Firms with more bureaucratic forms of eco-controls show a high level of alignment between environmental strategic intents and eco-practices, regardless of their environmental strategic intents. While firms with eco-marketing practices exhibit high environmental and economic performance, firms with eco-production practices show high environmental and economic performance only when they also adopt eco-marketing practices. The study extends existing literature by explicitly distinguishing between intended environmental strategy (i.e. environmental strategic intent) and realized environmental strategy (i.e. eco-practice) and extends the analysis to examine environmental and economic performance. For practical implication, it is recommended that firms should use more bureaucratic forms of eco-control, such as action control, formal control, and tight control, to create a strategic alignment of eco-practices, which in turn, will lead to high performance.